Gross domestic product - Garcés, Sandra (2014)
The national Gross Domestic Product (GDP) is analyzed by industry in the period 2000-2013. DOI: https://doi.org/10.31164/bcoyu.1.2014.529 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/529